Broch-Due, Vidgis and Margit Ystanes (eds.), Trusting and its Tribulations. Interdisciplinary Engagements with Intimacy, Sociality and Trust, New York: Berghahn Books, 2016, pp. 282. - Pawlik, Jacek (Studia Nauk Teologicznych PAN, 2020)
Nie wymagany